The Mathematical Model of Coupling Calculation the Electromagnetic Field and Heats of End Zone Powerful Turbogenerator - O. H. Kensytskyi; D. I. Hvalin; K. O. Kobzar (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
A quasi-three-dimensional field mathematical model of the electromagnetic field and heat transfer processes in end zone of a powerful turbogenerator has been developed. A model is the intermediate version between two-dimensional and three-dimensional solutions and is based on the numeral calculations in transversal and longitudinal sections of turbogenerator, interconnected by a complex of boundary conditions. On the first stage, a two-dimensional field model of the electromagnetic field in transversal section of central zone of a turbogenerator is considered. Then, taking into account the field distribution in central part, the magnetic field in longitudinal section is simulated. In response to the symmetry of the machine along axial and radial directions, the calculation area of end zone is considered as a half of the rotor section along its axis and the section of the stator core tooth in the tangential direction (circumferentially). Having taken the distribution of electromagnetic parameters obtained in the load mode of the machine as the initial data, the thermal losses in the elements and nodes of the end zone are determined. As a result of solving the joint problem of calculating the electromagnetic field and heat exchange processes, the distribution of heating has been obtained not only on the surface, but also inside the structural parts of the end zone. In particular, it has been found that the maximum temperature of 97.3 °C takes place in the tooth area of the end package of the stator core. This is explained by the combined effect of the main radial field, the axial leakage flux of the frontal portions of the stator and rotor windings, as well as by the “buckling” of a portion of the main flux out of the air gap. In addition, the pressure plate shielding effect is the cause of local field concentration in the toothed zone of the end package. The presented model makes it possible as early as at the design stage to evaluate the efficiency of design solutions for the formation of the end zone of the turbogenerator stator for different load modes of the machine, including the modes of consumption of reactive power.